Exegesis of development bureaucracy - Lund, John (2017)
The Swedish International Development Agency (Sida) is a governmental agency with the purpose to execute the Swedish international development aid. Sida plays a relatively large role in the international development scene and the governmental officials that work at Sida are representatives for the Swedish development politics. At the same time, the officials that supervise the foreign aid are individuals and thus to a degree autonomous subjects. This paper aims to explore the relation between formal bureaucratic space and subjective agency of these officials at the department for innovations and partnerships (PARTNER) at Sida. By doing extensive participatory observations, both as an intern and as an employee at the unit for research cooperation (FORSK) together with interviews and text analysis, this relation has been analysed. The analysis has been conducted with the help of Bourdieu’s theoretical framework concerning social fields and capitals together with Benford and Snow’s theoretical framework regarding collective action frames. The conclusion is that even though there are numerous layers of policies and guidelines to follow when working as a government official at Sida, the space for subjective agency is extensive. This space is instead ruled by unofficial, socially determined policies, which are a product as well as a producer of an office solidarity. This could very well be the result of a strong sense of togetherness sprung out of a somewhat exposed position and a niched workspace. Together the official and the unofficial guidelines create a social landscape which could help hold together and motivate the agency.